Posterior auricular myiasis: rare presentation of a malignant lesion / Mohamed Iliyas Sultan Abdul Kader ... [et al.] - Sultan Abdul Kader, Mohamed Iliyas; Mahbob, Hafiz Mohamad; Ahmad, Abd Razak; Mohamad, Irfan (Faculty of Medicine, 2022)
Squamous cell carcinoma (SCC) arises from the malignant proliferation of the keratinocytes of the epidermis that has invaded into the dermis or beyond. Posterior auricular SCC is categorized as high-risk SCC. Infestation of fly larvae or maggots in living tissue of humans and other vertebrate animals is known as myiasis. Rarity of the site of involvement with an underlying malignancy is the peculiarity of this case report. We present a case of elderly male with a posterior auricular mass with myiasis, which turns out to be SCC. Early detection and combined modality of aggressive treatment with surgery and radiation improves the overall patient survival rate.